Internet engagement and its association with weight parameters among Malaysian adolescents / Nurul Haniza Md. Yusof - Nurul Haniza, Md. Yusof (2019)
This study determines the prevalence of regular Internet engagement among Malaysian adolescents to study the socio-demographic variation in Internet engagement. It identifies the association of Internet engagement/time spent on the Internet with weight parameters (body mass index, body fat percentage and waist circumference) and academic performance (aggregate, Malay language, English language, mathematics subject, and science subjects) among adolescents in Malaysia. This is a cross-sectional study which used primary (academic performance) and secondary data from the second wave of the Malaysian Health and Adolescents Longitudinal Research Team (MyHeART) Study Cohort. Collected MyHeART data included the measurement of height, weight, body fat composition, waist circumference, and self-administered questionnaires. The participants comprised 720 students attending year three public secondary schools from the Kuala Lumpur, Selangor and Perak, Malaysia. Sampling was done using a two-stage cluster sampling design. The prevalence of adolescents who engage on the Internet regularly was 85.3% (n=614). Chinese (OR: 9.873, CI: 2.188-44.552) and Malays (OR: 2.379, CI: 1.332-4.251) significantly engaged regularly on the Internet compared to Indians. Adolescents who schooled in urban areas significantly engaged regularly on the Internet compared to adolescents schooled in rural areas (OR: 2.663, CI: 1.719 – 4.125). There was no significant association between Internet engagement or time spent on the Internet with weight-related parameters. Non-parametric test results recorded that the mean ranks of overall academic performance (aggregate) was significantly (p-value 0.017) higher (which indicate poor academic performance) in adolescents who rarely engaged on the iv Internet (413.50), compared to the adolescents who spent on average ≥3hours per day (350.70) and average <3hours per day on the Internet (352.11). A positive significant association between Internet engagement and academic performance was found for English (OR=2.184, CI=1.112-4.289), mathematic (OR=2.093, CI=1.012-4.329) and aggregate; overall academic performance (OR=2.319, CI=1.118-4.810). Although generally the trend of less likelihood on getting excellent and average on academic performance was observed among participants who spent an average of ≥3 hours per day on the Internet compared to participants who spent <3 hours daily on the Internet, however, it is non-significant. The significant findings of the association between time spent on the Internet with mathematics and aggregate were perhaps the effect of a bigger sample size during the estimation in the population. Furthermore, the confidence interval that was close to one indicated that the result might be statistically significant but not clinically significant in view of the minimal differences within each group. Internet engagement and time spent on the Internet do not associate with weight-related parameters. However, engagement on the Internet was found to be beneficial for academic performance. Nevertheless, close monitoring, supervision, and guidance on Internet engagement among adolescents were relevant.